Mechanical complications of shunt for hydrocephalus - Aline Saré de Melo (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: Hydrocephalus is the pathology most frequently addressed and studied in pediatric neurosurgery. Over 15,000 new cases are diagnosed each year. Although it is the most com-mon procedure performed by pediatric neurosurgeons, the shunt implant for drainage of cerebrospinal fluid (CSF) also presents the highest rate of failure and replenishment. The last 50 years have been marked by important advances in quality of these implants. How-ever, little has changed regarding the prevalence of these failures. We will comment here the main mechanical failures of the shunt: disconnection, migration, fracture and scrap-ing of the catheter, hollow visceral perforation and distal catheter knot.